1996
DOI: 10.1103/physrevd.54.2640
|View full text |Cite
|
Sign up to set email alerts
|

Gravitons and light cone fluctuations. II. Correlation functions

Abstract: A model of a fluctuating lightcone due to a bath of gravitons is further investigated. The flight times of photons between a source and a detector may be either longer or shorter than the light propagation time in the background classical spacetime, and will form a Gaussian distribution centered around the classical flight time. However, a pair of photons emitted in rapid succession will tend to have correlated flight times. We derive and discuss a correlation function which describes this effect. This enables… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
60
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 9 publications
1
60
0
Order By: Relevance
“…Decoherence due to electromagnetic fluctuations as a potential new quantum vacuum effect has long attracted attention with pioneering analysis reported in [30]. Theoretically, spacetime fluctuations must also exist due to the quantization of the metric field [31,32], though details may vary with presently uncertain theories of quantum gravity. In the linearized approximation of gravity, one hopes to draw valuable analogy with QED despite differences in certain details.…”
Section: Introductionmentioning
confidence: 99%
“…Decoherence due to electromagnetic fluctuations as a potential new quantum vacuum effect has long attracted attention with pioneering analysis reported in [30]. Theoretically, spacetime fluctuations must also exist due to the quantization of the metric field [31,32], though details may vary with presently uncertain theories of quantum gravity. In the linearized approximation of gravity, one hopes to draw valuable analogy with QED despite differences in certain details.…”
Section: Introductionmentioning
confidence: 99%
“…This approach can be used to treat the quantum fluctuations of the gravitational field, which has been a topic of much interest in recent years [12,13,14,15,16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Further, several authors [27][28][29][30][31] have suggested horizon oscillations (fluctuations) are generic phenomena in quantum gravity. Let us briefly comment on the existing literature.…”
Section: 휇]mentioning
confidence: 99%